Water quality and phytoplankton diversity of Gopeswar temple freshwater pond in Assam (India) (Bangladesh Journal of Botany, 2013)
Water quality and phytoplankton diversity were investigated in Gopeswar temple pond of Assam, India. Altogether 45 species of phytoplankton were recorded representing Chlorophyceae (16), Cyanophyceae (10), Bacillariophyceae (14), Euglenophyceae (3), Chrysophyceae (1) and Dinophyceae (1). Phytoplankton peaks were observed in summer and monsoon periods. Correlations of phytoplankton density with different water quality parameters were evaluated and the water body was found to be moderately polluted. Presence of Microcystis aeruginosa along with Navicula cryptocephala throughout the year also indicated its cultural eutrophication and hence, needs management intervention DOI: http://dx.doi.org/10.3329/bjb.v41i2.13446 Bangladesh J. Bot. 41(2): 181-185, 2012 (December)